ENHANCING EFL INDONESIAN STUDENTS’ WRITING ABILITY AND MOTIVATION THROUGH FACEBOOK-INKSHEDDING - Rahmah, Nur Alfa (English Department of Faculty of Tarbiyah and Teacher Training, 2015)
This paper is attempted to propose a breakthrough alternative in the EFL teaching to enhance students? ability and motivation in writing through facebook-inkshedding. The current development of technology and teenager?s close relationship with online social networking demands English instructor to be more creative in choosing the medium that suit the students? interest and teenage trend. Facebook nowadays possess a prominent position among other social network media that makes it a very potential learning media. Inkshedding, on the other side, is a very effective strategy to boast students? creative ideas and confidence in writing. It brings an active discussion into written form and trigger students to express their mind in the target language and make them get used of it gradually. Not only that facebook-inkshedding exists beyond time and physical boundary, it can also grow students? sense of community and motivate them to develop independently.